Tracer diffusion in the σ phase of the CoCrFeMnNi system. (15th January 2021) - Zhang, Jingfeng; Muralikrishna, G. Mohan; Asabre, Alex; Kalchev, Yordan; Müller, Julian; Butz, Benjamin; Hilke, Sven; Rösner, Harald; Laplanche, Guillaume; Divinski, Sergiy V.; Wilde, Gerhard
Abstract: A single Cr-rich σ-phase alloy with a composition of Co17 Cr46 Fe16.3 Mn15.2 Ni5.5 (at.%) and a tetragonal lattice structure was produced. The tracer diffusion coefficients of Ni and Fe were measured by secondary ion mass spectroscopy using the highly enriched 64 Ni and 58 Fe natural isotopes. On the homologous temperature scale, Ni and Fe diffuse in the σ phase faster as compared to the corresponding diffusion rates in the equiatomic and face-centered cubic CoCrFeMnNi alloy. In contrast, on the absolute temperature scale, these elements diffuse roughly at the same rates in both materials. Factors influencing element diffusion and phase stability of the σ phase compared to the equiatomic alloy are discussed. Graphical Abstract: Image, graphical abstract